Seismic visibility of carbonated subducted oceanic crust in the lower mantle - Yajie Zhao; Xin Deng; Wenzhong Wang; Zhongqing Wu; Ye Yuan (Communications Earth & Environment)
Abstract Seismological studies have previously detected abundant scatterers in the lower mantle, potentially linked to long-term slab subduction, and petrology studies suggest carbonates can be sequestrated within the oceanic crust and transported into the lower mantle via subduction. Here, we report ab initio calculations of elastic properties of calcium carbonate within various structures at lower-mantle conditions, as well as phase boundary between different calcium carbonate phases. Combining our results with previous data, we derived the density and wave velocities of carbonated oceanic crust, considering the possible reactions between carbonates and silicates. Our results suggest calcium carbonate high-pressure phases exhibit much lower density and wave velocities than other lower-mantle minerals. However, the moderately carbonated oceanic crust still displays positive wave velocity anomalies in the lower mantle, except at mid-mantle depths. Besides, the carbonated oceanic crust reaches similar shear wave velocity to the surrounding mantle at ~1100 km depth, which could explain the scarcity of seismic scatterers at this depth.